Escape rooms as an interactive learning experience: insights into designing a radiology-themed escape room and exit survey data. - Oppenheimer, Jonas; Lüken, Sophia; Bierbrauer, Annika; Kamieniarz, Paul; Nilssen, Martine S.; Bui, Maurice Quang Loc; Haack, Anna-Maria; Jahn, Mona; Beller, Katharina; Uluk, Yasmin; Grumberg, Lyel; Lerchbaumer, Markus Herbert; et al. (Insights into Imaging, 2025)
Objectives: Escape rooms provide an interactive learning experience, combining clinical knowledge with problem-solving and teamwork. A radiology-themed escape room has been organized at the European Congress of Radiology in 2019 and 2023–2025, with over 900 people participating in total. The process of developing a radiology-themed escape room is discussed, and the results of a participant survey are presented. Materials and methods: The development of a radiology-themed escape room was based on five steps. Initially, an overarching concept was chosen, then multiple puzzle ideas were brainstormed. These were linked together to form a story, and then fully developed with relevant images and materials. Finally, the room was tied together, and a fitting atmosphere was created. Participants in 2025 were asked to complete a survey with questions on their training status, the challenges that they found most difficult, and their thoughts on the activity as a learning tool and for improving teamwork. Results: Three different concepts of radiology-themed escape rooms were developed for the congresses from 2019 to 2025. The overarching concepts were a polytrauma situation, a thrombectomy for fulminant pulmonary embolism, and a tumor board, respectively. Two hundred ninety people participated in 2025, and 149 completed the exit survey; 66.7% of participants were able to complete the room in time. Enjoyment, learning, and team building were all rated highly by participants. Conclusion: A development process for designing a radiology-themed escape room is presented. A prior implementation shows an enjoyable and educational experience for radiologists and other medical professionals. Critical relevance: Insights are given on the development of a radiology-themed escape room, providing a unique interactive learning opportunity for residents that incorporates image interpretation with teamwork and cognitive puzzles, resulting in an enjoyable educational experience. Key Points: A step-by-step guide on developing a radiology-themed escape room is presented. Radiological escape rooms provide an enjoyable, educational, and team-building experience. Interactive learning experiences could play a larger role in modern radiology education.